ANALISIS KETERSEDIAAN AIR UNTUK TANAMAN TOMAT (Lycopersicum esculentum Mill) DAN JAGUNG (Zea mays L.) DI TONSEWER - Musa F. Zulkarnain; Karamoy Th. Lientje; Jody M. Mawara (Universitas Sam Ratulangi, 2017)
ABSTRACTThe study aims to analyze the adequacy of water in the area Tonsewer for the growth of tomato plants and corn. This research conducted in Tonsewer village, West Tompaso. Materials and equipment use are drill, ring sampels, hoes, sholves, machetes, laboratory equipment, sack,plastic, rubber, 10 years of climate data (monthly rainfall, humidity, watering time,wind speed, maximum and minimum temperatures), soil data, and plants data.The result using the model of CropWat8 that condition the availability of water for crops as tomatoes and corn sufficient available. Planting June 1st decreased soil moisture ahead of the third phase of growth of tomato plants.Tomato plants need sufficient water in the initiation phase/transplanting and in the initial phase until the final disposal phase of fruitformation. Planting time June 1st and July 1st the reduction soil moisture at planting time these two accurred in the third growth phase reach a position under conditions readily available in the fourth growth phase.Keywords : water availability, evapotranspiration, CropWat8 model